Comportamento informacional dos docentes e discentes do Programa de Pós-graduação em Física da Universidade Federal do Ceará - Silva, Giordana Nascimento de Freitas e (2018)
This dissertation deals with the information behavior of users of the Physics Course Library (BCF), members of the Postgraduate Program in Physics (PPGFIS) of the Federal University of Ceará (UFC). It presents the following guiding question: how do BCF users, linked to PPGFIS, behave in relation to the search and use of information? It was defined as a general objective to examine with more perceptiveness the informational behavior of the users of the Library of the Physics Course, linked to the Post-Graduation Program in Physics, Federal University of Ceará. In order to give answers on the problem question, the following specific objectives were established: a) to know the needs that guide the search and use of information; b) understand the modes of realization based on the model proposed by Carol Kuhlthau; c) verify the facilities found by users of the Physics Course Library; d) identify the difficulties experienced by users; and e) demonstrate the level of satisfaction of the users of the library regarding the meaning of the search and use of information. The research field was chosen due to the fact that the researchers act professionally in this environment, and we believe this enriched the analysis of the data and the establishment of relations between them. The whole idea was based on Carol Kuhtlhau's cognitive perspective, because we understood that thoughts, feelings and actions intrinsically permeate the Information Search Process (PBI). In order to fulfill the defined purposes, an exploratory and descriptive research of qualitative nature was carried out, configuring a case study, whose field of research was BCF and, therefore, as a unit of analysis, the users linked to PPGFIS (Postgraduate Program in Physics). The research sample comprised 09 (nine) teachers and 25 (twenty-five) students. The instrument of data collection was the survey applied via e-mail. Based on this methodological path, we present the following results: a) the information needs of the teachers are linked to the disciplines they teach and to the projects of the laboratories or research groups they coordinate; b) in the case of the students, their questions are associated to this scenario through the elaboration of theses and dissertations; c) the most favorable environment for researching new approaches in the field of physics was the internet; (d) on the other hand, the BCF acquis is a reference for consultation of the fundamental principles underlying the specialties of the area concerned; e) the time factor was the most present in the answers related to the difficulties encountered by teachers and students; and f) regarding the indicated facilities, we verified that the interaction capacity between the peers optimizes the location and selection of the materials of interest. From the above, we find the satisfaction of the public studied in conducting the Information Search Process, due to the evident 8 production and innovation of their research, whose results have been published in periodicals with a high impact factor and, consequently, characterized by high citation indexes.